Cooperative polariton dynamics in feedback-coupled cavities - Bimu Yao (Nature Portfolio, 2017)
Rabi oscillations of magnons typically do not have few photon control of single spin quantum systems. Here, the authors use a feedback cavity architecture to increase magnon-photon cooperativity, enabling increased control of light-matter interactions in magnonic systems via cooperative polariton dynamics.